Feedback from massive stars at low metallicities: MUSE observations of N44 and N180 in the Large Magellanic Cloud. Issue 4 (5th October 2018) - McLeod, A F; Dale, J E; Evans, C J; Ginsburg, A; Kruijssen, J M D; Pellegrini, E W; Ramsay, S K; Testi, L
ABSTRACT: We present MUSE integral field data of two H ii region complexes in the Large Magellanic Cloud: N44 and N180. Both regions consist of a main superbubble and a number of smaller, more compact H ii regions that formed on the edge of the superbubble. For a total of 11 H ii regions, we systematically analyse the radiative and mechanical feedback from the massive O-type stars on the surrounding gas. We exploit the integral field property of the data and the coverage of the He ii  λ5412 line to identify and classify the feedback-driving massive stars and from the estimated spectral types and luminosity classes we determine the stellar radiative output in terms of the ionizing photon flux Q 0 . We characterize the H ii regions in terms of their sizes, morphologies, ionization structure, luminosity and kinematics, and derive oxygen abundances via emission line ratios. We analyse the role of different stellar feedback mechanisms for each region by measuring the direct radiation pressure, the pressure of the ionized gas, and the pressure of the shock-heated winds. We find that stellar winds and ionized gas are the main drivers of H ii region expansion in our sample, while the direct radiation pressure is up to three orders of magnitude lower than the other terms. We relate the total pressure to the star formation rate per unit area, ΣSFR, for each region and find that stellar feedback has a negative effect on star formation, and sets an upper limit to ΣSFR as a function of increasing pressure.